2022
DOI: 10.1177/14648849221095335
|View full text |Cite
|
Sign up to set email alerts
|

The structures that shape news consumption: Evidence from the early period of the COVID-19 pandemic

Abstract: Researchers and practitioners increasingly believe that journalism must improve its relationship with audiences to increase the likelihood that people will consume and support news. In this paper, we argue that this assumption overlooks the importance of structural- and individual-level factors in shaping news audience behavior. Drawing on Giddens’ theory of structuration, we suggest that, when it comes to the amount of time that people devote to news, consumers’ choices are guided more by life circumstances t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Notably, although this second wave of interviews occurred after the pandemic had begun, we found no discernible difference in comments shared by participants in Wave 1 versus Wave 2; neither the interviewers nor the interviewees focused on the pandemic. This tracks with Comscore research showing that while Americans demonstrated higher-than-usual interest in news during the initial pandemic shutdowns of March and April 2020, by summer 2020, with many states fully reopened, news use had fallen back to more normal levels (Nelson and Lewis, 2022). As such, we deemed both sets of interviews to be adequately reliable.…”
Section: Methodsmentioning
confidence: 63%
See 1 more Smart Citation
“…Notably, although this second wave of interviews occurred after the pandemic had begun, we found no discernible difference in comments shared by participants in Wave 1 versus Wave 2; neither the interviewers nor the interviewees focused on the pandemic. This tracks with Comscore research showing that while Americans demonstrated higher-than-usual interest in news during the initial pandemic shutdowns of March and April 2020, by summer 2020, with many states fully reopened, news use had fallen back to more normal levels (Nelson and Lewis, 2022). As such, we deemed both sets of interviews to be adequately reliable.…”
Section: Methodsmentioning
confidence: 63%
“…This article sought to understand the everyday experiences of news audiences (Kammer, 2020; Madianou and Miller, 2013; Peters and Schrøder, 2018). Amid the “audience turn” in journalism studies, researchers have focused on the experiences of news users in connection with dimensions such as the COVID-19 pandemic and its impact (Nelson and Lewis, 2021; Nelson and Lewis, 2022), democracy and civic engagement (Wagner and Boczkowski, 2019), and growing forms of news avoidance (Edgerly, 2017). Comparatively less scholarship has focused on the experiences of why people might not share the news they encounter.…”
Section: Methodsmentioning
confidence: 99%
“…It is common during difficult times for people to use social media frequently or to seek social support online (Mowbray, 2020). During a crisis, people often search for event-related data to stay informed (Purgato et al, 2018;Nelson & Lewis, 2022). The 2020 COVID-19 pandemic affected people's online news consumption.…”
Section: Engagement On Digital Platforms During the Pandemicmentioning
confidence: 99%
“…The possibility of audiences to interact with journalists made journalists more aware of their needs and desires, influencing decisions about which content should be produced (Ferrer-Conill and Tandoc Jr 2018: p. 437). Journalists – and journalism scholars – agree that “journalism must improve its relationship with audiences” (Nelson and Lewis 2022: p. 1). In light of these evolutions, Hanitzsch and Vos (2017) propose to approach journalism as a discursive institution: an institution shaped by how the audience speaks of and interacts with it (Hanitzsch and Vos 2017: p. 121).…”
Section: Introductionmentioning
confidence: 99%
“…Although the ‘audience turn’ (Costera Meijer, 2020) in journalism has been extensively discussed in studies, and journalists acknowledge the need to improve their relationship with their audience (Nelson and Lewis 2022), the audience’s perspective on journalistic roles remains underexplored (Riedl and Eberl, 2020). Generally, the examination of journalistic roles has been from a production perspective (Hanusch 2019).…”
mentioning
confidence: 99%